Enhanced bentonites for containment of inorganic waste leachates by GCLs. Issue 4 (2nd July 2018) - Scalia, J.; Bohnhoff, G. L.; Shackelford, C. D.; Benson, C. H.; Sample-Lord, K. M.; Malusis, M. A.; Likos, W. J.
Abstract : The sensitivity of sodium bentonite (Na-B) to adverse chemical interactions has spurred development of enhanced bentonites (EBs) for geosynthetic clay liners (GCLs) that provide superior properties for containment systems. EB-GCLs are engineered to control contaminant transport by maintaining low hydraulic conductivity ( k ) when exposed to solutions with high ionic strength, a preponderance of divalent cations, and/or extreme pH (<2 and >12). An overview of current EB-GCL technologies is provided. Engineering properties, including k, the effective diffusion coefficient ( D *), and the membrane or chemico-osmotic efficiency coefficient ( ω ), are summarized for EBs and compared to properties of conventional Na-B. Applicability of indicator parameters currently used to assess GCLs containing Na-B (swell index, fluid loss, and liquid limit) is evaluated for EBs. Mechanisms proven or postulated to influence the behavior of EBs are presented and discussed. EBs generally have superior transport properties (lower k, lower D *, higher ω ) in elevated concentration solutions, although some bentonites amended with proprietary additives (broadly termed contaminant resistant clays, or CRCs) have been found to be similar or inferior to Na-B. Compatibility tests conducted with containment liquids are necessary to assess the transport properties of EB-GCLs for site-specific applications.